Preparation and Characterization of Petai Pods Extract (Parkia speciosa Hassk.) Loaded Ethosomes - Fitrya Fitrya; Najma Annuria Fithri; Annisa Amriani; Annisa Haryati; Dina Permata Wijaya (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2021)
Preparation of petai pods extract (Parkia speciosa) into ethosome aim to increased penetration through the skin. The method of cold is used in preparing petai pods extract encapsulation by ethosome with variation in concentration of soya lecithin, propylene glycol, and ethanol. The proportion of optimum formula ethosome consisted were 0,2 g soya lecithin, 1 ml propylene glycol, and 4 ml ethanol that response values obtained pH of 4,74, viscosity of 0,950 cP, %EE of 74,326%, and stability of 7,288%. The resulted of optimum formula obtained were PDI of 0,23, zeta potential of -7,5 mV, and particle size of 818,7 nm. Ethosome showed spheric particle using Transmissin Electron Microscopy. The diffusion analysis showed highest on ethosome of petai pods extract (9,525%) than petai pods extract (5,466%). The interaction study used FTIR show no chemical interaction extract pods and ethosome components